TEORI KEADILAN RESTORATIF (RESTORATIVE JUSTICE) SEBAGAI UPAYA PELINDUNGAN TERHADAP ANAK YANG BERHADAPAN DENGAN HUKUM (STUDI PENYELESAIAN KASUS PIDANA ANAK DI POLRES TANJUNG PINANG) - Tiara Annisa Pri Elja (Prodi Ilmu Hukum Fakultas Hukum Universitas Muhammadiyah Riau, 2022)
This study discusses the position of restorative justice theory in the regulation and application of juvenile criminal acts. There are several other studies related to the discourse discussed in this study. but by looking at these studies, this paper explores the position of restorative justice theory in the regulation and application of juvenile crimes.This research is a normative legal research using a statutory, conceptual, and case approach. the legal sources used are primary legal sources used are laws and regulations relating to the topic of this research. and also uses several other legal sources, namely secondary legal sources in the form of journals, books and literature related to this research.The analysis in this study uses qualitative analysis, namely the analysis of the data obtained for research using the technical analysis of qualitative data is generally subjective. In qualitative research, researchers get data from many sources and use many methods as is the case with several literatures, books, journals related to this research. This study discusses 1) the Urgency of Restorative Justice in Handling Cases of Children Dealing with and 2) Barriers to the Application of Restorative Justice in Criminal Cases of Children Confronting the Law at the Tanjungpinang Police.